Petrogenetic elements of El Carmen granodiorite. Northeast Merida City, Merida state, Venezuela - Tazzo Rangel, María; Hoeger, Tábata; Andara, íngel; Maninat, María (Rev. Téc. Fac. Ing. Univ. Zulia, 2012)
The El Carmen Granodiorite (Upper Triassic) is an igneous body that extends for about 40 km from Capilla del Carmen Sector northwest of Merida city, until the head of Turmero river, near Pico El íguila area. The granitic mass has a linear shape, featuring sinuous gradational intrusive contact with Iglesias Complex schists (Neoproterozoic), and abrupt fault contact with both sedimentary formations of Cretaceous and Paleogene, and with Iglesias Complex. From a mineralogical and textural point of view, this granitoid is an homogeneous body with coarse to medium-grained phaneritic texture. It can be found local tonalitic, monzogranitic and pegmatitic dikes, which are generally a little more than one meter thick, and cogenetic with El Carmen Granodiorite. Chemical analysis indicate that this granitoid is peraluminous and calc-alkaline, being the result of partial melting of metapelites which gives it an S-type granitoid character, with a possible basaltic contamination. Its emplacement was synorogenic, and probably occurred in a volcanic arc tectonic setting, associated with the western edge of Pangea.